A Comparative Treatment Results of Oesophageal Squamous Cell Carcinoma by Neoadjuvant Chemotherapy followed by Radiotherapy versus Radiotherapy Alone - Salam, B; Perveen, I; Faruque, GM; Mohammed, AKMG (Journal of Medicine, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Background: Studies suggest that neoadjuvant chemotherapy prior to radiotherapy results in improved response and survival in large primary lesion. This study aimed to evaluate the role of neoadjuvant chemotherapy prior to radiotherapy in patients with localized oesophageal cancer. Method: In this randomized controlled study 60 selected cases of oesophageal squamous cell carcinoma were randomized to Arm-A & Arm-B. Patients assigned to combination therapies(Arm- A) received two cycles (4 weekly) of injectable 5- fluorouracil(400mg/m2/day for five days ) and mitomicin C (7mg/ m2 on D1) as neoadjuvant chemotherapy prior to radiotherapy(44GY in 22 fractions). Patients of Arm-B received radiotherapy alone as in arm-A. Treatment responses were compared following completion of treatment at six and 12 weeks. Complete response was defined as no difficulty in swallowing and no visible growth in follow-up barium swallow X-Ray. Partial response was defined as difficulty in swallowing semisolids but not liquids and persistence of residual growth in barium swallow X-Ray. Results: The study initially enrolled 68 patients but eight patients dropped out. Complete response occurred in 66.6% (20) patients who received combination therapies (n=30), where as in 40% (12) patients who received radiotherapy alone (P= < 0.05). Partial response occurred in 33.33% patients assigned to have pre-irradiation chemotherapy and in 60% patients having radiotherapy alone. Toxicities like dysphagia, anorexia, vomiting was more in combination therapy group, but it was acceptable. Conclusion: Neoadjuvant chemotherapy followed by radiation therapy demonstrated better response than radiation alone at the expense of toxicity in patients with localized oesophageal cancer. Â DOI = 10.3329/jom.v8i2.1409 J MEDICINE 2007; 8 : 60-63